Retinal Blood Flow Velocity Change in Parafoveal Capillary after Topical Tafluprost Treatment in Eyes with Primary Open-angle Glaucoma - Iida, Yuto; Akagi, Tadamichi; Nakanishi, Hideo; Ohashi Ikeda, Hanako; Morooka, Satoshi; Suda, Kenji; Hasegawa, Tomoko; Yokota, Satoshi; Yoshikawa, Munemitsu; Uji, Akihito; Yoshimura, Nagahisa (Scientific reports, 2017)
Although ocular circulation at the retina and optic disc is known to be associated with the pathology of glaucoma, direct measurement of blood flow velocity has been difficult to obtain. This prospective observational study enrolled 11 consecutive patients with treatment-naïve primary open-angle glaucoma (POAG) and 11 healthy subjects, and the effects of topical tafluprost treatment on ocular circulation were examined at baseline and at 1, 4, and 12 weeks after initiating treatment with topical tafluprost on POAG patients using multiple modalities, which include adaptive optics scanning laser ophthalmoscopy (AOSLO). Baseline mean intraocular pressure (IOP) was significantly higher and mean parafoveal blood flow velocity (pBFV) was significantly lower in POAG eyes than in healthy eyes. Mean IOP was significantly decreased (1 week, −19.1%; 4 weeks, −17.7%; and 12 weeks, −23.5%; all P < 0.001) and mean pBFV was significantly increased from the baseline at all follow-up periods after initiating treatment (1 week, 14.9%, P = 0.007; 4 weeks, 21.3%, P < 0.001; and 12 weeks, 14.3%, P = 0.002). These results reveal that tafluprost may not only lower IOP but may also improve retinal circulation in POAG eyes and AOSLO may be useful to evaluate retinal circulatory change after treatment.